Crystal structures of (Et4N)2C2S6, (Et4N)2C2S5, (Et4N)2CS4, (Et4N)HCS3, (Et4N)2CS3 ⋅ 2H2O and (Et4N)2CS4‐y ⋅ yH2O (y=0.69). Issue 7 (2nd February 2021) - Bernhardt, Eduard
Abstract: The crystal structures of (Et4 N)2 C2 S6, (Et4 N)2 C2 S5, (Et4 N)2 CS4, (Et4 N)HCS3, (Et4 N)2 CS3  ⋅ 2H2 O and (Et4 N)2 CS4‐y  ⋅ yH2 O (y=0.69) were determined by single‐crystal X‐ray diffraction analysis at 150 K. For the first time, salts with the C2 S5 2− and HCS3 − anions could be synthesized. Abstract :